The Metacognitive Strategy to Achieve Listening Comprehension in Kulni Modern Islamic Boarding School - Munawar Tanjung, Muhamad Farhan; Heryatun, Yayu; Sa’diah, Siti (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
Metacognitive is the process of thinking about our minds, which is how a process, and control that information to find new understanding/knowledge and seek relationships with other knowledge. The purpose of this study is to discover how students in class XI of Kulni Modern Islamic Boarding School at Cikande, Serang Banten in use English listening metacognitive strategies, as well as the differences in improving English listening comprehension among students before and after receiving metacognitive learning. The population of this study included 61 students from class XI ofÂ Kulni Modern Islamic Boarding School at Cikande, Serang Banten.Â The sample consisted of 29 students from A class XI. The researcher used quantitative data analysis in this study. Data is gathered by administering tests to the class. There are two kinds of tests: pre-test and post-test. According to the study’s findings, the average pre-test score at researcher Modern Islamic Boarding School at Cikande, Serang Banten was 40.41, and the average post-test score in the experimental class was 57.21. Based on the data presented above, it is possible to conclude that there is a 41.5 percent change in learning outcomes. Based on the result of the study, applying metacognitive strategies for learning can help students become interested in listening activities and can be an alternative innovation in learning listening.